Extensive Listening Practice in EFL Classroom with Variety of News Websites - Yusawinur Barella; Andini Linarsih (State Institute for Islamic Studies IAIN of Metro, 2020)
One potential of extensive online listening materials is that, unlike intensive listening, EFL students can listen independently by using audio listening features. It encourages students to practice listening and to promote listening fluency and autonomous learning outside the classroom. However, little research has investigated how lower English proficiency students from non- English department in EFL setting, undertaking the process of extensive listening. This study requires some Indonesian students at the tertiary level to select the appropriate materials with their proper level of listening speed to the individual learner. It was a weekly assignment to practice listening outside their classroom. This study seeks to investigate the websites that the EFL students with low proficiency levels choose to do their extensive listening activities, the types of news that may interest the students to listen, and the perception of the extensive listening activities. The results showed that students use captioned- provided websites as their media instruction in listening for pleasure with a variety of news.